A National Study of Leadership in the Irish Primary Sector: STEM Education and Wellbeing during Crisis - Fahy, Amy (Trinity College Dublin. School of Education. Discipline of Education, 2022)
Principals are leaders in school communities and their role is becoming increasingly more autonomous. Specifically, the role of the principal is evolving given the continuous implementation of new reforms and policies. This dissertation seeks to explore the leadership role of principals in the context of STEM education and crisis management. By drawing on Ability, Motivation and Opportunity (AMO) Framework and Relational Coordination (RC) Theory, this dissertation makes an original contribution to knowledge by answering the following research questions: (1) How do principals influence or promote STEM education? (2) How does principal leadership influence their own wellbeing, and their school’s performance during the Covid-19 crisis? To do so, this research is organised into two studies. Study 1: Leadership in STEM Education, which builds on and contributes to knowledge in the influencing of and promotion of STEM education. For example, although studies have examined STEM education, limited research has explored how transformational leadership can be effective in influencing improved STEM implementation in school settings. Following this, Study 2: Leadership during the COVID-19 Crisis, contributes to existing literature supporting the importance of developing effective leadership in times of crisis. For instance, despite the number of studies focused on organizational leadership during crises, few have explored if transformational leadership is effective for organizational changes and crisis-management. Overall, this dissertation contributes to knowledge around principals and policy or initiative implementation by offering new and original contributions to this field. Furthermore, the studies reveal current leadership practices and insights on STEM education and crisis management.
Keywords: Leadership; STEM; Primary School; COVID-19